Solid Pseudopapillary Neoplasm of the Pancreas in a Pediatric Patient. (September 2015) - Stanley, Parker; Stanley, Charles; Ciambotti, Jon; LeGallo, Robin; Altes, Talissa
Solid pseudopapillary neoplasm (SPN) is a rare epithelial neoplasm of the pancreas, with low malignant potential, that usually occurs in young women. With advancing diagnostic imaging techniques and technology, the number of documented SPN cases has increased. Due to a varying morphologic appearance, SPNs often fail to show typical imaging findings, making it difficult to establish a definitive diagnosis. A case is reported of a SPN discovered on a routine abdominal sonogram, further characterized with magnetic resonance imaging, and confirmed with surgical pathology analysis. Sonographers should be aware of this rare pathology and should consider SPN in the differential diagnosis when encountering an indeterminate pancreatic neoplasm, especially in a young female patient.